A comparative analysis of quasi-static indentation and low-velocity impact on the free edges of CFRP composite laminates - Li, Nian; Du, Jian; Liu, Rui; Lee, Hsiao Mun; Lee, Heow Pueh (Composites. Part B, Engineering, 2025)
A comparative study was conducted to evaluate the feasibility of using quasi-static indentation for characterizing the dynamic behavior of CFRP laminated composites subjected to free edge-on impact, focusing on both damage resistance and tolerance. Inspection methods, including ultrasonic C-scanning, 3D X-ray CT reconstruction, in-situ DIC measurement, etc., were utilized to examine damage status and mechanical responses induced by quasi-static edge-on indentation, dynamic edge-on impact and subsequent compression. The analysis revealed comparable failure mechanisms underlying the quasi-static and dynamic testing: wedge-shaped debris and bending fracture of the sub-laminates. In compression, local buckling of sub-laminates caused delamination propagation, ultimately resulting in structural collapse due to fiber fracture. Quasi-static testing provided a good approximation of dynamic edge-on force-displacement behavior without force signal oscillations. A compressive strength reduction of approximately 30 %, for barely visible impact damage (BVID) induced by edge-on loading, emphasized the significance of edge-on impact damage tolerance, where the more accessible quasi-static method could be employed.